PP02 Cost-Effectiveness of New left Ventricular Assist Devices (LVADS) for Patients with advanced Heart Failure: Analysis of the UK NHS Bridge to Transplant (BTT) programme. (10th September 2013) - Clarke, A; Pulikottil-Jacob, R; Connock, M; Suri, G; Kandala, N-B; Maheswaran, H; Banner, N; Sutcliffe, P
Abstract : Background: Public health measures aim to prevent people from reaching tertiary prevention or palliative or heroic care. Nevertheless these remain the only options for some people. There is an expanding population with very severe heart failure and although heart transplant is the optimal treatment, this option is dependent on a diminishing supply of donor hearts. For more than a decade, the NHS has supported the transplant programme for patients awaiting a donor heart with a 'bridge to transplant' programme - surgical implantation of a mechanical pump to support left ventricular function called a Left Ventricular Assist Device (LVAD). Alternatively individuals waiting for a heart receive medical management with drugs such as intravenous inotropes. Methods: A semi-Markov multi-state economic model was built using NHS costs data and data for patients listed for transplant in the UK NHS Blood and Transplant Data Base (BTDB). Quality adjusted life years (QALYs) gained and incremental cost per QALY were calculated for patients receiving LVADs compared to those receiving medical management with inotrope support. Results: Patients were mainly white: 86%; male 84.2% (95% CI 79.4, 88.0) and middle aged - mean age 50.8 years (49.3, 52.4). BMI was 26.5 (25.7, 27.3). 25.2% (17.4, 35.1) patients had diabetes. 83.5% (78.0, 87.9) had the highest level of heart failure (NYHA Class IV). 235 patients received a second or third generation LVAD between 2002 -2012 of whom 14% received a heart transplant. 307 patients received medical management and 67% received a transplant. LVADs conferred improved survival compared to medical management. LVADs cost £80, 569 per device at 2011 prices. Estimated probabilistic incremental cost effectiveness ratio (ICER) was £53, 527/QALY (£31, 802, £94, 853) over a lifetime horizon. Estimates were sensitive to choice of comparator, likelihood of receiving a transplant and time to transplant. Reducing device cost by 15% brought the ICER down to £50, 106/QALY. Discussion: New left ventricular assist devices (LVADs) deliver greater health benefits at higher cost than medical management in the UK. Cost-effectiveness estimates are hampered by the lack of randomised comparative evidence. Relatively small reductions in costs of LVADs would bring them into line with other interventions for end of life care already recommended for adoption within the UK NHS by NICE. National Institute for Health Research, UK. Project number HTA 12/02/01.